The Development of the Judicial Awareness of the Governing Elite of the Grand Duchy of Lithuania in the mid-16th Century (1529–1566) - Vaitkus, Tomas (Lietuvos istorijos studijos, 2018)
[article in Lithuanian; only abstract and key words in English] Codification processes in The Grand Duchy of Lithuania during the 16th century show a rapid transformation of judicial awareness. In this case, the shift of the judicial awareness of the governing elite was caused by few conditions that distinguished this sociopolitical stratum from the estate of nobles. First, members of the governing elite were judges and consumers of the judicial system, while the rest of the nobility were just consumers; this caused a formation of a binary relation with the law. Second, the higher political and social-economical position provided advantages in a judicial process and supported a hierarchical approach to the courts of law, which could cause judicial nihilism in the perception of law and justice. Third, members of the governing elite represented different political groups, had different political, social and economic potential, had become members of this group through different means; these and other individual experiences had eclecticized the legal awareness. These conditions generated a symbiosis of archaic and new judicial ideas, which formed a qualitatively new perception of law, justice and the judicial.